Silicon-carbon negative electrode material and preparation method and application thereof
By using a silicon-carbon anode material composed of porous carbon matrix and silicon particles in the battery negative electrode material, and forming an ultra-thin silicon layer between its core and the carbon layer, the problem of serious volume expansion of the silicon-based anode material during charging and discharging is solved, and a high stability and high capacity battery anode material is achieved.
Patent Information
- Application Number
- CN202411944200.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-18
AI Technical Summary
The volume expansion of the silicon-based negative electrode material during charging and discharging is severe, affecting the stability of the electrode material and the maintenance of battery capacity.
A silicon carbon negative electrode material is used, and its core consists of a porous carbon matrix and silicon particles loaded in the porous carbon matrix. The silicon element content is 30%-60%. An ultra-thin silicon layer is formed between the core of the silicon carbon negative electrode material and the carbon layer, and the volume expansion rate is controlled to be less than 5%.
The volume expansion rate is less than 5% during the charging and discharging process, while maintaining a high capacity, improving the stability and capacity performance of the negative electrode of the battery.
Smart Images

Figure CN119852354A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery negative electrode materials, and in particular to silicon-carbon negative electrode materials and preparation methods and applications thereof. Background Art
[0002] In recent years, with the application of large-scale electrical equipment, people have put forward higher requirements for battery life, fast charging and safety performance. Silicon-based negative electrode materials have attracted widespread attention due to their high specific capacity and wide source of raw materials. However, silicon materials will produce huge volume expansion during the charging and discharging process, which seriously affects the stability of electrode materials during the cycle process and causes rapid decay of battery capacity. Summary of the invention
[0003] Based on this, it is necessary to provide a silicon-carbon negative electrode material and its preparation method and application to address the above problems; the silicon-carbon negative electrode material has a specific structure and silicon element content, and its volume expansion rate during charging and discharging can be less than 5%, and its capacity is relatively high, and it can be used in the battery negative electrode to achieve excellent stability and high capacity.
[0004] A silicon-carbon negative electrode material, comprising a core and a silicon layer and a carbon layer sequentially coated on the surface of the core, wherein the core comprises a porous carbon matrix and silicon particles loaded in the porous carbon matrix, wherein the silicon content of the silicon-carbon negative electrode material is 30%-60%, the silicon content of the core is 15%-50%, and the thickness of the silicon layer accounts for 0.1%-15% of the radius of the silicon-carbon negative electrode material.
[0005] In one embodiment, the ratio of the silicon content of the core to the silicon content of the silicon-carbon negative electrode material is 1:2-17:20.
[0006] In one embodiment, the density of the silicon particles in the pores of the porous carbon matrix is ρ′=m / v, where m is the mass of the silicon particles, v is the pore volume of the porous carbon matrix, and ρ′ is 0.3 g / cm 3 -0.5g / cm 3 .
[0007] In one embodiment, the porosity of the silicon-carbon negative electrode material is less than 20%;
[0008] And / or, the density of the silicon-carbon negative electrode material is 0.7 g / cm 3 -1.1g / cm 3 .
[0009] In one of the embodiments, in the silicon-carbon negative electrode material, the core also includes amorphous carbon supported in the porous carbon matrix.
[0010] In the silicon-carbon negative electrode material described in the present invention, there is an ultra-thin silicon layer between the core and the carbon layer, and the overall silicon content is 30%-60%. At the same time, in the core of the silicon-carbon negative electrode material, the silicon content can reach up to 50%. This specific silicon particle filling structure not only enables the silicon particles to be fully filled in the pores of the porous carbon matrix, but also has a certain volume space to accommodate the volume expansion of the silicon particles, so that the volume expansion rate of the silicon-carbon negative electrode material during the charge and discharge process can be less than 5%, and the capacity is relatively high, which can achieve excellent stability and high capacity when used in the battery negative electrode.
[0011] A method for preparing the silicon-carbon negative electrode material as described above comprises the following steps:
[0012] Providing porous carbon, and mixing the porous carbon with a silicon source pyrolysis catalyst to obtain a mixture, wherein the silicon source pyrolysis catalyst is selected from at least one of ammonium salts or tertiary amine compounds;
[0013] Under the conditions of protective gas and silicon source gas, the mixture is subjected to a vapor deposition reaction at 150° C.-350° C., and after the deposition is completed, a carbon source gas is introduced to prepare a carbon coating layer to obtain a silicon-carbon negative electrode material.
[0014] In one embodiment, the mass fraction of the silicon source pyrolysis catalyst in the mixture is 1%-20%;
[0015] And / or, the pore volume of the porous carbon is 0.2 cm 3 / g-1.5cm 3 / g;
[0016] And / or, the specific surface area of the porous carbon is 500m 2 / g-2500m 2 / g.
[0017] In one embodiment, the vapor deposition reaction satisfies at least one of the following conditions:
[0018] (1) The volume ratio of the protective gas to the silicon source gas is 0.5:1-10:1;
[0019] (2) The flow rate of the protective gas is 0.1L / min-10L / min;
[0020] (3) The protective gas is selected from nitrogen and / or argon;
[0021] (4) The silicon source gas is selected from monosilane and / or disilane;
[0022] (5) The vapor deposition reaction time is 1h-10h.
[0023] The preparation method of the present invention, on the one hand, uses ammonium salts or tertiary amine compounds as silicon source pyrolysis catalysts, which is beneficial to reduce the activation decomposition energy of Si-H bonds, so that the temperature of the vapor deposition reaction is as low as 150°C-350°C, and silicon is deposited at a lower reaction temperature, which is beneficial to inhibit the excessive growth and excessive agglomeration of silicon grains, and refine the size of the deposited silicon grains, which is beneficial to significantly reduce the volume expansion rate of the obtained silicon-carbon negative electrode material during the charge and discharge process; on the other hand, the silicon source pyrolysis catalyst is mixed with porous carbon. During the deposition process, since the silicon source pyrolysis catalyst is inside the porous carbon, it can promote more silicon deposition into the inside of the porous carbon at a lower temperature, thereby making the silicon content inside the silicon-carbon negative electrode material higher, which is more conducive to exerting higher capacity performance. In addition, compared with the preparation process with a traditional vapor deposition reaction temperature higher than 400°C, the preparation method of the present invention is also beneficial to reduce the preparation cost and has more economic benefits.
[0024] A negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer, wherein the negative electrode active material layer comprises the silicon-carbon negative electrode material as described above.
[0025] A battery comprises the negative electrode sheet as described above. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 This is a scanning electron microscope image of the silicon-carbon negative electrode material prepared in Example 1, with a scale of 1 μm;
[0028] Figure 2 This is the X-ray diffraction pattern of the silicon-carbon negative electrode material prepared in Example 1. DETAILED DESCRIPTION
[0029] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific implementation methods or embodiments and are not intended to limit the present invention.
[0031] The present invention provides a silicon-carbon negative electrode material, comprising a core of the silicon-carbon negative electrode material and a silicon layer and a carbon layer sequentially coated on the surface of the core, wherein the core comprises a porous carbon matrix and silicon particles loaded in the porous carbon matrix, wherein the silicon content of the silicon-carbon negative electrode material is 30%-60%, the silicon content of the core is 15%-50%, and the thickness of the silicon layer accounts for 0.1%-15% of the radius of the silicon-carbon negative electrode material.
[0032] In the silicon-carbon negative electrode material described in the present invention, there is an ultra-thin silicon layer between the core and the carbon layer, and the overall silicon content is 30%-60%. At the same time, in the core of the silicon-carbon negative electrode material, the silicon content can reach up to 50%. This specific silicon particle filling structure not only enables the silicon particles to be fully filled in the pores of the porous carbon matrix, but also has a certain volume space to accommodate the volume expansion of the silicon particles, so that the volume expansion rate of the silicon-carbon negative electrode material during the charge and discharge process can be less than 5%, and the capacity is relatively high, which can achieve excellent stability and high capacity when used in the battery negative electrode.
[0033] Specifically, the silicon content of the silicon-carbon negative electrode material includes but is not limited to any point value among 30%, 32%, 35%, 38%, 40%, 43%, 45%, 47%, 50%, 53%, 55%, 60% or any range value between two of them; the silicon content of the inner core includes but is not limited to any point value among 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or any range value between two of them; the thickness of the silicon layer accounts for a percentage of the radius of the silicon-carbon negative electrode material including but not limited to any point value among 0.1%, 1%, 5%, 8%, 10%, 15% or any range value between two of them, preferably 0.1%-10%, which can not only make the silicon-carbon negative electrode material maintain good conductivity, but also can improve the overall capacity, which is beneficial to improve the compatibility of the silicon-carbon negative electrode material and the positive electrode material.
[0034] It can be understood that the silicon content of the core is less than the silicon content of the silicon-carbon negative electrode material, and the sum of the silicon content of the core and the silicon content of the silicon layer is equal to the silicon content of the silicon-carbon negative electrode material.
[0035] Preferably, the ratio of the silicon content of the core to the silicon content of the silicon-carbon negative electrode material is 1:2-17:20, including but not limited to any point value among 1:2, 3:5, 7:10, 4:5, 17:20 or a range value between any two of them.
[0036] In one embodiment, the density of the silicon particles in the pores of the porous carbon matrix is ρ′m / v, where m is the mass of the silicon particles, v is the pore volume of the porous carbon matrix, and ρ′ is 0.3 g / cm 3 -0.5g / cm 3 By regulating the distribution of silicon particles in the pores of the porous carbon matrix, the content of silicon particles loaded in the porous carbon matrix is made higher, which is not only beneficial to improve the utilization rate of the pores in the porous carbon matrix, but also provides a certain space for the expansion of silicon particles, thereby further improving the capacity and stability.
[0037] Specifically, the density ρ′ of the silicon particles in the pores of the porous carbon matrix includes but is not limited to 0.30 g / cm 3 , 0.32g / cm 3 , 0.35g / cm 3 , 0.38g / cm 3 , 0.40g / cm 3 , 0.42g / cm 3 , 0.45g / cm 3 , 0.47g / cm 3 , 0.50g / cm 3 Any point value in or any range value between two values, more preferably 0.80g / cm 3 -1.50g / cm 3 .
[0038] In one embodiment, when the silicon particles are primary particles, the particle size of the primary particles is preferably 5nm-50nm, including but not limited to any point value among 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm or any range value between two of them.
[0039] In one embodiment, when the silicon particles are secondary particles formed by agglomeration of primary particles, the particle size of the secondary particles is preferably less than 100 nm, including but not limited to any point value among 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm or a range value between any two of them.
[0040] In one embodiment, the porosity of the silicon-carbon negative electrode material is preferably less than 20%, for example, any point value among 5%, 8%, 9%, 10%, 11%, 15%, 16%, 17%, 19.6% or any range value between two thereof, so that the silicon-carbon negative electrode material has a certain silicon particle loading while maintaining a certain porosity, which is more conducive to exerting a higher capacity performance.
[0041] In one embodiment, the density of the silicon-carbon negative electrode material is 0.7 g / cm 3 -1.1g / cm 3 , for example 0.7 g / cm 3 , 0.8g / cm 3 , 0.9g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 Any point value in or any range of values between them.
[0042] In one embodiment, in the silicon-carbon negative electrode material, the pore volume of the porous carbon matrix is preferably 0.2 cm 3 / g-1.5cm 3 / g, for example 0.2cm 3 / g, 0.3cm 3 / g, 0.4cm 3 / g, 0.5cm 3 / g, 0.6cm 3 / g, 0.7cm 3 / g, 0.8cm 3 / g, 0.9cm 3 / g, 1.0cm 3 / g, 1.1cm 3 / g, 1.2cm 3 / g, 1.3cm 3 / g, 1.4cm 3 / g, 1.5cm 3 Any point value in / g or any range of values between them.
[0043] In one embodiment, in the silicon-carbon negative electrode material, the specific surface area of the porous carbon matrix is preferably 500 m 2 / g-2500m 2 / g, for example 500m 2 / g、700m 2 / g、900m 2 / g、1100m 2 / g, 1300 2 / g、1500m 2 / g、1700m 2 / g、1900m 2 / g, 2100m 2 / g, 2300m 2 / g、2500m 2 Any point value in / g or any range of values between them.
[0044] By regulating the porosity, density, pore volume and specific surface area of the silicon-carbon negative electrode material and the porous carbon matrix, it is beneficial for the silicon particles to reach a specific filling volume in the pores of the porous carbon matrix, thereby reducing the volume expansion rate and increasing the capacity.
[0045] In one embodiment, the inner core further comprises amorphous carbon supported in the porous carbon matrix. It should be noted that the present invention does not limit the specific distribution state of the amorphous carbon.
[0046] The present invention provides a method for preparing the silicon-carbon negative electrode material as described above, comprising the following steps:
[0047] S1, providing porous carbon, and mixing the porous carbon with a silicon source pyrolysis catalyst to obtain a mixture, wherein the silicon source pyrolysis catalyst is selected from at least one of ammonium salts or tertiary amine compounds;
[0048] S2, under the conditions of protective gas and silicon source gas, subjecting the mixture to a vapor deposition reaction at 150° C.-350° C., introducing a carbon source gas after the deposition to prepare a carbon coating layer, and obtaining a silicon-carbon negative electrode material.
[0049] The preparation method described in the present invention, on the one hand, adopts ammonium salt or tertiary amine compound as silicon source pyrolysis catalyst, which is beneficial to reduce the activation decomposition energy of Si-H bond, so that the temperature of vapor deposition reaction is as low as 150°C-350°C, and silicon is deposited at a relatively low reaction temperature, which is beneficial to inhibit excessive growth and excessive agglomeration of silicon grains, refine the size of deposited silicon grains, and significantly reduce the volume expansion rate of the obtained silicon-carbon negative electrode material during the charge and discharge process; on the other hand, the silicon source pyrolysis catalyst is mixed with porous carbon. During the deposition process, since the silicon source pyrolysis catalyst is inside the porous carbon, it can promote more silicon deposition into the interior of the porous carbon at a relatively low temperature, thereby making the silicon content inside the silicon-carbon negative electrode material higher, which is more conducive to exerting higher capacity performance.
[0050] In addition, compared with the traditional preparation process with a vapor deposition reaction temperature higher than 400° C., the preparation method of the present invention is also beneficial for reducing preparation costs and is more economical.
[0051] In step S1, the mass fraction of the silicon source pyrolysis catalyst in the mixture is preferably 1%-20%, for example, any value among 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or a range between any two values, more preferably 5%-15%.
[0052] Specifically, when the silicon source pyrolysis catalyst is selected from ammonium salts, the ammonium salts include but are not limited to at least one of ammonium chloride (NH4Cl) and ammonium fluoride (NH4F); when the silicon source pyrolysis catalyst is selected from tertiary amine compounds, the tertiary amine compounds include but are not limited to at least one of triethylamine, triethylenediamine, N,N-dimethylaniline, and N,N-diethylaniline.
[0053] It should be noted that the present invention does not limit the preparation method of porous carbon, and it can be prepared by conventional processes, for example: mixing an organic compound with a base, heat treating it under an inert atmosphere, and acid-washing the product to obtain porous carbon, wherein the organic compound is preferably a natural organic compound, more preferably cellulose, and the base is preferably potassium bicarbonate.
[0054] In one embodiment, the pore volume of the porous carbon is preferably 0.2 cm 3 / g-1.5cm 3 / g, for example 0.2cm 3 / g, 0.3cm 3 / g, 0.4cm 3 / g, 0.5cm 3 / g, 0.6cm 3 / g, 0.7cm 3 / g, 0.8cm 3 / g, 0.9cm 3 / g, 1.0cm 3 / g, 1.1cm 3 / g, 1.2cm 3 / g, 1.3cm 3 / g, 1.4cm 3 / g, 1.5cm 3 Any point value in / g or any range of values between them.
[0055] In one embodiment, the specific surface area of the porous carbon is preferably 500 m 2 / g-2500m 2 / g, for example 500m 2 / g、700m 2 / g、900m 2 / g、1100m2 / g, 1300 2 / g、1500m 2 / g、1700m 2 / g、1900m 2 / g, 2100m 2 / g, 2300m 2 / g、2500m 2 Any point value in / g or any range of values between them.
[0056] In step S2, the temperature of the vapor deposition reaction includes but is not limited to any point value among 150℃, 160℃, 180℃, 200℃, 210℃, 230℃, 250℃, 280℃, 300℃, 320℃, 340℃, 350℃ or any range value between any two of them.
[0057] In one embodiment, the vapor deposition reaction satisfies at least one of the following conditions:
[0058] (1) The volume ratio of the protective gas to the silicon source gas is 0.5:1-10:1, for example, any value among 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, and 10:1, or a range between any two values;
[0059] (2) The flow rate of the protective gas is 0.1 L / min-10 L / min, for example, 0.1 L / min, 0.5 L / min, 1 L / min, 2 L / min, 3 L / min, 4 L / min, 5 L / min, 6 L / min, 7 L / min, 8 L / min, 9 L / min, 10 L / min, any point value therein or a range value between any two thereof;
[0060] (3) The protective gas includes but is not limited to nitrogen and / or argon;
[0061] (4) The silicon source gas includes but is not limited to monosilane and / or disilane;
[0062] (5) The time of the vapor deposition reaction is 1 h-10 h, for example, any value among 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h or a range between any two of them.
[0063] The present invention also provides a negative electrode plate. The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer, and the negative electrode active material layer includes the silicon-carbon negative electrode material as described above. It is understandable that the negative electrode active material layer may also include materials such as a conductive agent and a binder, and the present invention does not limit this.
[0064] It should be noted that the present invention does not limit the preparation method of the negative electrode sheet, and it can be prepared using conventional processes.
[0065] The present invention also provides a battery. The battery includes the negative electrode sheet as described above. It is understandable that the battery also includes a positive electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet, the separator and the electrolyte can adopt any conventional commercially available positive electrode sheet (or positive electrode material), the separator and the electrolyte, and the present invention is not limited to this.
[0066] The present invention further provides an electrical device, comprising the battery as described above.
[0067] It is understandable that the above-mentioned power usage settings include any equipment that uses the above-mentioned batteries, such as electric vehicles, power tools, electronic products, energy storage systems, and office equipment, but are not limited thereto.
[0068] The silicon-carbon negative electrode material, its preparation method and application will be further described below through the following specific examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention. If no specific conditions are specified in the examples, they are carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.
[0069] Example 1
[0070] 500 g of KHCO3 and 100 g of cellulose were fully mixed and placed in an oven for drying. Then, they were placed in a tubular furnace and heat treated at 400 °C for 6 h under an inert atmosphere. The collected black powder was then reacted in 1 mol / L hydrochloric acid for 6 h, then rinsed with ethanol and deionized water three times respectively, and filtered and dried to obtain porous carbon.
[0071] 100g of porous carbon was fully mixed with 10g of NH4Cl, and the mixed powder was placed in a tube furnace and vapor deposited at 400℃ for 4h in a silane and argon atmosphere, wherein the gas flow rate of silane was 1L / min and the gas flow rate of argon was 1L / min. After the silane deposition was completed, acetylene gas with a flow rate of 1L / min was introduced and reacted at 550℃ for 2h. After the reaction was completed, it was cooled to room temperature to obtain a silicon-carbon negative electrode material. The prepared material was characterized by SEM and XRD tests, and the results were as follows: Figure 1 and Figure 2 shown.
[0072] Example 2
[0073] The porous carbon was prepared in the same manner as in Example 1.
[0074] 100g of porous carbon was fully mixed with 10g of NH4F, and the mixed powder was placed in a tube furnace and vapor deposited at 400℃ for 4h in a monosilane and argon atmosphere, wherein the gas flow rate of monosilane was 1L / min and the gas flow rate of argon was 2L / min. After the silane deposition was completed, acetylene gas with a flow rate of 1L / min was introduced, and the reaction was carried out at 550℃ for 2h. After the reaction was completed, it was cooled to room temperature to obtain a silicon-carbon negative electrode material.
[0075] Example 3
[0076] The porous carbon was prepared in the same manner as in Example 1.
[0077] 100g of porous carbon was fully mixed with 10g of triethylenediamine, and the mixed powder was placed in a tube furnace and vapor deposited at 400℃ for 4h in a silane and argon atmosphere, wherein the gas flow rate of silane was 1L / min and the gas flow rate of argon was 5L / min. After the silane deposition was completed, acetylene gas with a flow rate of 1L / min was introduced, and the reaction was carried out at 550℃ for 2h. After the reaction was completed, it was cooled to room temperature to obtain a silicon-carbon negative electrode material.
[0078] Example 4
[0079] The porous carbon was prepared in the same manner as in Example 1.
[0080] 100g of porous carbon was fully mixed with 10g of NH4F, and the mixed powder was placed in a tube furnace and vapor deposited at 400℃ for 2h in a monosilane and argon atmosphere, wherein the gas flow rate of monosilane was 1L / min and the gas flow rate of argon was 2L / min. After the silane deposition was completed, acetylene gas with a flow rate of 1L / min was introduced, and the reaction was carried out at 550℃ for 2h. After the reaction was completed, it was cooled to room temperature to obtain a silicon-carbon negative electrode material.
[0081] Example 5
[0082] The porous carbon was prepared in the same manner as in Example 1.
[0083] 100g of porous carbon was fully mixed with 10g of NH4F, and the mixed powder was placed in a tube furnace and vapor deposited at 400℃ for 6h in a monosilane and argon atmosphere, wherein the gas flow rate of monosilane was 1L / min and the gas flow rate of argon was 2L / min. After the silane deposition was completed, acetylene gas with a flow rate of 1L / min was introduced, and the reaction was carried out at 550℃ for 2h. After the reaction was completed, it was cooled to room temperature to obtain a silicon-carbon negative electrode material.
[0084] Example 6
[0085] The porous carbon was prepared in the same manner as in Example 1.
[0086] 50g of porous carbon was fully mixed with 10g of NH4F, and the mixed powder was placed in a tube furnace and vapor deposited at 400℃ for 10h in a monosilane and argon atmosphere, wherein the gas flow rate of monosilane was 1L / min and the gas flow rate of argon was 5L / min. After the silane deposition was completed, acetylene gas with a flow rate of 1L / min was introduced, and the reaction was carried out at 550℃ for 2h. After the reaction was completed, it was cooled to room temperature to obtain a silicon-carbon negative electrode material.
[0087] Example 7
[0088] The difference between Example 7 and Example 1 is that the temperature of the vapor deposition reaction is 300°C.
[0089] Example 8
[0090] The difference between Example 8 and Example 1 is that the temperature of the vapor deposition reaction is 450°C.
[0091] Example 9
[0092] The difference between Example 9 and Example 1 is that the amount of NH4Cl is 1 g.
[0093] Example 10
[0094] The difference between Example 10 and Example 1 is that the amount of NH4Cl is 2.5 g.
[0095] Comparative Example 1
[0096] 500 g of KHCO3 and 100 g of cellulose were fully mixed and placed in an oven for drying. Then, they were placed in a tubular furnace and heat treated at 400 °C for 6 h under an inert atmosphere. The collected black powder was then reacted in 1 mol / L hydrochloric acid for 6 h, then rinsed with ethanol and deionized water three times respectively, and filtered and dried to obtain porous carbon.
[0097] 50 g of porous carbon was placed in a tubular furnace and vapor deposited at 400°C for 4 hours in a monosilane and argon atmosphere, wherein the gas flow rate of monosilane was 1 L / min and the gas flow rate of argon was 1 L / min. After the reaction was completed, it was cooled to room temperature to obtain a silicon-carbon negative electrode material.
[0098] Comparative Example 2
[0099] 500 g of KHCO3 and 100 g of cellulose were fully mixed and placed in an oven for drying. Then, they were placed in a tubular furnace and heat treated at 400 °C for 6 h under an inert atmosphere. The collected black powder was then reacted in 1 mol / L hydrochloric acid for 6 h, then rinsed with ethanol and deionized water three times respectively, and filtered and dried to obtain porous carbon.
[0100] 50 g of porous carbon was placed in a tubular furnace and vapor deposited at 500°C for 4 hours in a monosilane and argon atmosphere, wherein the gas flow rate of monosilane was 1 L / min and the gas flow rate of argon was 1 L / min. After the reaction was completed, it was cooled to room temperature to obtain a silicon-carbon negative electrode material.
[0101] Comparative Example 3
[0102] The difference between Comparative Example 3 and Example 1 is that the same mass of ferric chloride is used as the silicon source pyrolysis catalyst.
[0103] The silicon-carbon negative electrode materials prepared in Examples 1 to 10 and Comparative Examples 1 to 3 were tested, and the results are shown in Table 1 and Table 2, respectively. The specific testing methods are as follows.
[0104] (1) Silicon content test: Weigh about 1g of sample, put it into a box-type resistance furnace, heat it from room temperature to 1200℃ at a heating rate of 20℃ / min, burn it for 8h, burn it to constant weight, and then calculate the content of silicon content according to the formula w Si =[(m3-m1) / m2]×(Ar / M)×100% The silicon content of the silicon-carbon negative electrode material is calculated, wherein m1 is the mass of the crucible, m2 is the mass of the sample, m3 is the total mass of the crucible and the sample after burning to constant weight, Ar is the relative atomic mass of silicon, and M is the relative molecular mass of silicon dioxide; the thickness of the silicon layer is observed by TEM, and then the surface is etched by designing the concentration of hydrofluoric acid and etching time to obtain the core of the silicon-carbon negative electrode material, and the silicon content of the core is obtained by the same method.
[0105] (2) Density test: Weigh the mass of the measuring cylinder, recorded as m1, place the sample to be tested in the measuring cylinder, and place the measuring cylinder on the vibration device. Use a clamp with a guide rod to tighten the measuring cylinder. Vibrate 3000 times with an amplitude of 3 mm and a vibration frequency of 100 to 300 times per minute until the volume of the sample in the measuring cylinder remains unchanged. If the surface of the sample is horizontal after compaction, read the value directly. If the surface of the sample is not horizontal after compaction, read the highest and lowest values, and calculate their average value to obtain the compacted volume V. Remove the measuring cylinder and weigh the total mass of the measuring cylinder and the sample after compaction again, recorded as m2. Calculate the density of the silicon-carbon negative electrode material according to the formula ρ = (m2-m1) / V.
[0106] (3) Pore volume, porosity and specific surface area test: Refer to the standard GB / T19587 gas adsorption BET method for determining the specific surface area of solid substances in the physical and chemical test room.
[0107] (4) Radius and silicon layer thickness of silicon-carbon negative electrode material: obtained through TEM test observation. It should be noted that the radius and thickness are average values obtained from multiple tests.
[0108] (5) Density ρ′ of silicon particles in the pores of porous carbon matrix: Taking a sample of about 1 g as a benchmark, the mass m of silicon particles in the inner core can be obtained according to test method (1), and the pore volume v of the porous carbon matrix can be obtained according to test method (3). Based on this, the density of silicon particles in the pores of the porous carbon matrix is calculated by ρ′=m / v.
[0109] Table 1
[0110]
[0111]
[0112] Table 2
[0113]
[0114] Application Examples
[0115] The silicon-carbon negative electrode materials prepared in Examples 1 to 10 and Comparative Examples 1 to 3 were used to prepare button-type batteries in the following manner: the silicon-carbon composite material was used as the active material, the metal lithium sheet was used as the counter electrode, and the CR2032 button-type battery was assembled in a glove box, the polypropylene microporous membrane was used as the diaphragm, and the electrolyte was a conventional silicon-carbon electrolyte. The electrochemical performance of the battery was tested using constant current charge and discharge technology (GCD). The voltage window was 0.005-1.5V, and the test current density was 0.1C.
[0116] The assembled button cell was subjected to a performance test, and the results are shown in Table 3.
[0117] Table 3
[0118]
[0119] According to Table 3, Examples 1 to 3 use ammonium salts and tertiary amine compounds as silicon source pyrolysis catalysts, and all of them can achieve the technical effect of depositing silicon at a lower reaction temperature. Comparative Examples 4 to 6, in the case of low-temperature silicon deposition with the same NH4F catalyst, adjusting the deposition time to 2h, 4h, 6h, and 10h, respectively, can achieve good deposition effects, achieving a volume expansion rate of less than 5% and a higher capacity. When the deposition time is 4h, the performance of the obtained silicon-carbon negative electrode material is better.
[0120] It can be seen from Comparative Example 1 that, without adding a catalyst and at the same reaction temperature as in Example 1, monosilane is difficult to be thermally decomposed, resulting in almost no deposition of silicon into the porous carbon.
[0121] It can be seen from Comparative Example 2 that, without adding a catalyst and meeting the conventional pyrolysis temperature of silane, the silicon content deposited in the porous carbon is high, the silicon grain size is large, and the porosity is affected. Compared with Example 1, the volume expansion effect of Comparative Example 2 is aggravated.
[0122] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0123] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A silicon-carbon negative electrode material, characterized in that: The silicon-carbon negative electrode material includes a core and a silicon layer and a carbon layer sequentially coated on the surface of the core, the core includes a porous carbon matrix and silicon particles loaded in the porous carbon matrix, wherein the silicon content of the silicon-carbon negative electrode material is 30%-60%, the silicon content of the core is 15%-50%, and the thickness of the silicon layer accounts for 0.1%-15% of the radius of the silicon-carbon negative electrode material.
2. The silicon-carbon negative electrode material according to claim 1, characterized in that: The ratio of the silicon content of the core to the silicon content of the silicon-carbon negative electrode material is 1:2-17:
20.
3. The silicon-carbon negative electrode material according to claim 1, characterized in that: The density of the silicon particles in the pores of the porous carbon matrix is ρ′=m / v, where m is the mass of the silicon particles, v is the pore volume of the porous carbon matrix, and ρ′ is 0.3 g / cm 3 -0.5g / cm 3 .
4. The silicon-carbon negative electrode material according to claim 1, characterized in that: The porosity of the silicon-carbon negative electrode material is less than 20%; And / or, the density of the silicon-carbon negative electrode material is 0.7 g / cm 3 -1.1g / cm 3 .
5. The silicon-carbon negative electrode material according to claim 1, characterized in that: In the silicon-carbon negative electrode material, the core also includes amorphous carbon supported in the porous carbon matrix.
6. A method for preparing a silicon-carbon negative electrode material according to any one of claims 1 to 5, characterized in that: The steps include: Providing porous carbon, and mixing the porous carbon with a silicon source pyrolysis catalyst to obtain a mixture, wherein the silicon source pyrolysis catalyst is selected from at least one of ammonium salts or tertiary amine compounds; Under the conditions of protective gas and silicon source gas, the mixture is subjected to a vapor deposition reaction at 150° C.-350° C., and after the deposition is completed, a carbon source gas is introduced to prepare a carbon coating layer to obtain a silicon-carbon negative electrode material.
7. The method for preparing the silicon-carbon negative electrode material according to claim 6, characterized in that: The mass fraction of the silicon source pyrolysis catalyst in the mixture is 1%-20%; And / or, the pore volume of the porous carbon is 0.2 cm 3 / g-1.5cm 3 / g; And / or, the specific surface area of the porous carbon is 500m 2 / g-2500m 2 / g.
8. The method for preparing the silicon-carbon negative electrode material according to claim 6, characterized in that: The vapor deposition reaction satisfies at least one of the following conditions: (1) The volume ratio of the protective gas to the silicon source gas is 0.5:1-10:1; (2) The flow rate of the protective gas is 0.1L / min-5L / min; (3) The protective gas is selected from nitrogen and / or argon; (4) The silicon source gas is selected from monosilane and / or disilane; (5) The vapor deposition reaction time is 1h-10h.
9. A negative electrode plate, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer, and the negative electrode active material layer comprises the silicon-carbon negative electrode material according to any one of claims 1 to 5.
10. A battery, characterized in that: Comprising the negative electrode sheet as claimed in claim 9.